E-Module Problem Solving Assisted by Virtual Home Lab Learning on Dynamic Electricity Material to Improve Understanding of Concepts - Azizahwati; Muhammad Sahal; M. Rahmad; Harlipadensi (Jurnal Edutech Undiksha, 2023)
Limited teaching materials, tools, and interactive physics learning media. These limitations certainly affect learning outcomes, causing students' low understanding of the material they study, specifically dynamic electricity. This research aims to create a physics e-module based on problem-solving and assisted by a virtual home learning lab on dynamic electrical materials. This type of research is Research and Development (R&D) using the ADDIE model. The subjects in this research were 3 expert validators, 2 teachers, and 20 students in practicality trials. The assessment instruments used are validation sheet questionnaires and teacher and student practicality assessment sheets. The data analysis techniques in this research are qualitative and quantitative descriptive analysis techniques. This research produced an average e-module validation score in the valid category, namely 3.57, and the average e-module practicality score in the practical category, namely 3.71 and 3.67, by teachers and students. The results of this research are that e-modules can be categorized as valid and practical, so they are suitable for use in learning. Development of e-modules based on problem-solving on dynamic electricity material to increase students' understanding of concepts to achieve the expected goals. This research implies that the e-module developed can be used as alternative teaching material by teachers and students in Physics subjects in class IX SMP, especially dynamic electricity material.